Dimensionen des Wissens im Recht - Münkler, Laura (Mohr Siebeck, 2019)
Knowledge is both a prerequisite of law and a challenge for it. The contributions in this volume shed light on the various dimensions of the relationship between law and knowledge, assessing the ways in which knowledge has been generated, structured and processed within law.
PublicationDate: 20190520
Keywords: Information -- Wissensgenerierung -- coinage -- Holiness Code -- Nichtwissen -- Technikgeschichte -- Elektrizitätsdiebstahl -- Wissensverarbeitung -- Gemeinnutz -- Zunft -- Sachverstand -- Rechtstheorie -- Verwaltungsrecht -- Besonderes Verwaltungsrecht -- Europarecht